Proton pump inhibitor usage is associated with higher all-cause mortality and CV events in peritoneal dialysis patients. Issue 1 (31st December 2022) - Zeng, Yingsi; Liu, Lingling; Zhu, Liya; Zhan, Xiaojiang; Peng, Fenfen; Feng, Xiaoran; Zhou, Qian; Zhang, Yujing; Wang, Zebin; Liang, Jianbo; Li, Jiao; Wen, Yueqiang
Abstract: Objectives: A long period of inappropriate proton pump inhibitors (PPI) treatment has been proved to be associated with adverse prognosis in general population and hemodialysis patients. This study was conducted to clarify the impact of PPI usage on mortality and adverse cardiovascular (CV) events in peritoneal dialysis (PD) patients. Methods and design: This is a retrospective study. A total of 905 patients were enrolled from two PD centers, including 211 patients on PPI treatment and 618 patients not on PPIs. Kaplan–Meier curves were used to identify the incidence of adverse outcomes. Multivariate Cox regression models and inverse probability of treatment weighting (IPTW) were applied to analyze hazard ratios (HRs) for adverse outcomes. Results: During follow-up, 162 deaths and 102 CV events were recorded. Kaplan–Meier curve demonstrated all-cause mortality (log-rank test p  = .018) and CV events (log-rank test p  = .024) were significantly higher in PPI usage group. Multivariate Cox regression models and IPTW showed that PPI usage was an indicator for all-cause mortality (HR = 1.35, 95%CI = 1.09–1.67, p  = .006) and CV events (HR = 1.78, 95%CI = 1.35–2.32, p  < .001). Conclusions: PPI usage is associated with higher all-cause mortality and CV events in PD patients. Clinicians are supposed to be more careful when using PPI and need to master the indications more rigorously in patients receiving PD treatment.